The Essence of the Modular Competency Approach in Training Workers (Journal of Educational Sciences, 2019)
The theme of the research work is the essence and importance of the modular competence approach in the training of workers. The aim of the research is the theoretical substantiation of the value of modular competence approach in improving the efficiency of training. In addition, the consideration of domestic experience in the application of modular training, which is the basis of modular and competence-based approach, the analysis of foreign experience, scientific-pedagogical literature on a modular competency-based approach, consideration of the application of modular competency-based approach in college defines the objectives of the study. The main focus of the work is the disclosure of the concept of “modular competence approach” in the training of a working specialist. The leading idea of the study: in the case of the introduction of modular competence approach in the process of training of workers, professional competence of the future specialist is formed and in modern conditions it is possible to train a specialist that meets the needs of the labor market. On the topic analyzed domestic and foreign pedagogical literature, the content analysis of the concepts of “module”, “competence”, “approach”, on the basis of which the author’s definition of the concepts of “module”, “competence”, “approach” and “modular competence approach”, not systematized in the scientific and pedagogical literature. In particular, the meaning of the term “approach”, which has not been studied so far in the literature in the Kazakh language. The authors came to it by content analysis of the analogue in Russian.Key words: modular training, modular competence approach, training of the working specialist, content analysis.